Perceived festival quality and revisit intention of Chinese New Year festival among generation Z / Chai Ming Na and Hasan Mohamed Zakaria - Chai, Ming Na; Mohamed Zakaria, Hasan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
This research investigates the perceived quality of Chinese New Year festivals in Malaysia from the perspective of Generation Z attendees. By employing quantitative surveys and the FESTPERF scale, the study explores various aspects of festival quality, including accessibility, facilities, ambiance, festival experience, entertainment program, food quality, staff, information, and technology experiences. The findings reveal a strong correlation between perceived festival quality and revisit intentions among Generation Z. Specifically, the study demonstrates that a positive festival experience, characterized by factors such as atmosphere and innovative technology, significantly influences Generation Z's desire to return to future events. These insights offer valuable recommendations for festival organizers seeking to enhance their events and attract a larger young audience.